Wetland Saline Water and Acid Mine Drainage Desalination by InterlayeFree Silica Pectin Membrane from Banan Peels - Elma, Muthia; Akhbar; Mustalifah, Fitri Ria; Suryani, Lilis; Rampun, Erdina Lulu Atika; Rahma, Aulia (Nusantara Science and Technology Proceedings)
Wetland water and acid mine drainage are available in South Kalimantan, Indonesia. However, “Wetland saline water (WSW)” phenomena occur in the wetland areas due to the seawater intrusion, this water which contains a high salt concentration is unsafe to be consumed. While acid mine drainage (AMD) pollution becomes an issue in the mining industry that impact human life and the environment. Salt particles could be removed by using a silica pectin membrane. Banana peel has a high pectin substance. Banana pectin (0.5wt% and 0.1wt%) was employed in silica and calcined at 300 and 400 °C. We demonstrate the silica pectin template’s performance without interlayer for wetland water and acid mine drainage desalination. Membranes were developed through a sol-gel method with silica source deposited from tetraethyl orthosilicate (TEOS) and performed by pervaporation at room temperature (~25 °C). As a result, 0.5wt% banana pectin concentration at 300 °C exhibited excellent performance with the highest water fluxes are 8.4 and 10.4 kg m?2 h?1 for WSW and AMD, respectively. Nevertheless, both membranes achieved high salt rejections up to 92%. Thereby, banana pectin as a carbon source impacts the stronger silica bond.